A decision support system for QoS-enabled distributed web services architecture - Wu, Chen; Chang, Elizabeth; Thomson, Patricia (IEEE, 2005)
Service selection is crucial for fulfilling the requirements of service requestors. While in the real service-oriented environment, Quality of Services (QoS) is one of the greatest concerns for consumers during service selection. Existing web services "standards do not tackle the QoS issue adequately when service discovery and selection are performed. In this paper, we argue that the process of services selection is a kind of decision making" to decide which service should be selected dependent on their QoS and trustworthiness values as well as their functional capabilities. Hence, we propose a service selection solution which utilizes the Decision Support Systems Module (DSS Module) to select the most appropriate service. In DSS module we introduce Service Trust to carry out the service QoS measurement based on the Context-specific Quality Aspects. The architecture of DSS module is presented in detail and the solution is also integrated into one of the components "domain broker" in our proposed distributed web services architecture. The contributions of this paper are two fold. Firstly, we apply DSS module into web services, thus opening a new, fertile ground for DSS research in web services literature and secondly, we provide a novel and feasible solution for QoS-based service selection.